Protagonismo de estudantes com deficiência em atividades extracurriculares: o caso da UFSCar - Saldanha, Luciléia Bechmann (2024)
Faced with the assumptions of inclusive education at all levels of schooling, which began in the 1990s, this research focuses on the participation of students with disabilities in extracurricular activities in higher education, in other words, the inclusion of these students in non-compulsory activities offered by the university. In an attempt to elucidate these matters, the investigation presented here set out to identify and analyze the conditions for the inclusion and participation of students with disabilities in extracurricular activities at UFSCar. The specific objectives are: I) To understand, from the participants perspective, how they engage in extracurricular activities; II) To characterize the profile of the participants, outlining their personal, academic and post participation experiences in extracurricular activities; III) To reflect on the path of access and participation of students with disabilities in extracurricular activities. In addition to a bibliographical survey and analysis of federal regulations, the main data was collected by means of a questionnaire aimed at all students with disabilities at UFSCar, in order to verify eligibility criteria; and interviews with students who met the established criteria. Two students agreed to take part in the interview, one with autism spectrum disorder and the other with a physical disability, aged 26 and 43, of different genders, from different academic areas and campi. The interviews were conducted in june 2023 via Google Meet and lasted an average of one hour. The survey was publicized through the course coordinators, the General Secretariat for Affirmative Action, Diversity and Equity and the Social Communication Coordination. The methodological approach adopted was qualitative and exploratory-descriptive. The interviews were transcribed and then analyzed based on four central axes: I) characterization on the participants; II) academic context; III) extracurricular activities; IV) considerations about university in the participants' lives. The results show that extracurricular activities acted in diverse ways in the participants' lives, highlighting the students' socio-historical issues intrinsic to the demands of academic life. To this end, we conclude that, in addition to federal regulations proposing that certain activities should be compulsory as part of the curriculum, it is necessary to identify the existing obstacles that prevent students, especially those with disabilities, from taking part in extracurricular activities, and when they do, it is not in a satisfactory way.